Research on optimal two element exchange algorithm for large scale cloud computing server scheduling problem - Wanliang WANG; Zelin ZANG; Guoqi CHEN; Hangyao TU; Yule WANG; Linyan LU (Tongxin xuebao)
With the flourishing of cloud computing industry,the rational management and scientific scheduling of cloud computing servers has become an important issue.In terms of model,a new mixed integer programming (MIP) model with affinity constraints and anti-affinity constraints was proposed to describe the scheduling problem of large scale cloud computing server.Considering the time cost of solving large-scale MIP problems,an optimal two element exchange algorithm was designed with the basics of branch and bound method and local search algorithm.By constantly extracting MIP sub-problems from completing scheduling problems and using branch and bound method to solve the sub-problems,the algorithm continuously optimized the server scheduling schemes,so that the scheduling schemes approached the optimal solution.The experimental results show that the algorithm has great advantages over the other methods in testing data set ALISS,and can reduce the resource consumption of cloud computing center by more than 4% when the same task is completed.